Peningkatan Hasil Belajar Jaring-Jaring Balok dan Kubus dengan Pendekatan PMRI di Kelas V SD Sabbihisma Padang - Halim, Helda; Harun, Mardiah; Masniladevi, Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This research is motivated by low mathematics learning outcomes. The purpose of this study was to describe an increase in mathematics learning outcomes consisting of: (1) planning, (2) implementation, (3) Learning Outcomes. The approach used is the approach of Pendidikan Matematika Realistik Indonesia (PMRI). Research subject of fifth grade students at SD Sabbihisma Padang. The results showed an increase in learning outcomes in the first cycle of meeting I 66.2%, experienced an increase in the first cycle of meeting II to 70.9%, and experienced an increase in the second cycle of meeting I to 90.9%. It can be concluded that the Pendidikan Matematika Realistik Indonesia approach can improve the learning outcomes of beam and cube nets in the fifth grade of SD Sabbihisma Padang.